Evidence that an episodic mode of thinking facilitates encoding of perceptually rich memories for naturalistic events relative to a gist-based mode of thinking. Issue 10 (26th November 2019) - Grilli, Matthew D.; Coste, Sedona; Landry, Janet E.; Mangen, Kathryn
ABSTRACT: Several studies have demonstrated that an episodic specificity induction (ESI) can influence cognitive abilities that involve episodic processes at retrieval. To better understand the downstream implications of an "episodic mode of thinking, " we investigate whether an ESI influences encoding of new events. In a between-subjects design, participants were given an ESI or gist (control) induction. In an ostensibly unrelated task, participants then were shown film clips of naturalistic events. After a filled delay, participants were given a surprise memory test, which required narrative recollection of the film clips. Participants who received the ESI generated narratives that contained more perceptual details specifically. Relative to gist thinking, an episodic mode of thinking appears to facilitate encoding of perceptually rich memories for naturalistic events.